Literasi Politik Komisi Pemilihan Umum Dalam Meningkatkan Partisipasi Pemilih Pemula Di Kota Samarinda - Amrullah, Fakhri; Dwivayani, Kadek Dristiana; Nurliah, Nurliah; Sucipta, Johantan Alfando Wikandana (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
This study is motivated by the important role of first-time voters in shaping democracy, who often face limitations in information and understanding of the election process. The purpose of this research is to analyze the role of political literacy conducted by the General Election Commission (KPU) of Samarinda City in increasing the participation of first-time voters through Instagram. The study employs a qualitative approach with data collected through interviews, observations, and documentation. The findings reveal that KPU Samarinda has implemented various political literacy programs, including outreach in schools, utilization of Instagram, and democracy training for youth. However, challenges such as low political interest among young voters and limited resources remain obstacles. In conclusion, the political literacy efforts by KPU positively contribute to raising awareness and participation of first-time voters, though strengthening strategies and cross-sector collaboration are needed for more optimal outcomes.